Industrial training report: Mesiniaga Berhad (Subang Jaya) / Aisyah Ramli - Ramli, Aisyah (Perpustakaan Tengku Anis, 2017)
Based on this period from 02 February 2017 to 30 June 2017 at Information Technology (IT) Department, edotco group, Special Project entitled, User Guide of Manage Engine Service Desk Plus and User Guide Manage Engine of Asset Management have been proposed for the staff of edotco's Bangladesh. Implementation of this was to propose was first, to standardize the classification of ticketing in terms oflog ticket and to move from manual to systematic process by integrated with user of edotco Group Sdn Bhd and edotco Bangladesh. Apart from that, Asset management operation in Manage Engine also functioned to asset in and out by making sure the leasing or contract date of an asset. Other than that, there were also task involve IT Service Desk and End User Computing (EUC) in IT Support team by making sure edotco's business continuity.